Analysis of the Implementation of the Kelurahan Bersinar Program in Depok City, West Java Province - Susanti , Anna Maria; Prastyawan, Agus; Pangaribuan, Nurmala (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Describe and analyze the extent and extent of influence relationship between communication factors, resources, implementer attitudes, bureaucratic structure towards the implementation of Kelurahan Bersinar in Depok city. This research is a research using a quantitative approach using the explanatory survey method. The sample required is 400. The instruments in this study are questionnaires and interview guidelines. The method used in data analysis and hypothesis testing in this study is by using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results of the study indicate thatcommunication, resources, disposition, and bureaucracy affect the implementation of the policy of implementing the Kelurahan Bersinar program in Depok. So that every program activity can run well and optimally, the village in Depok must pay attention to these four factors.